2021
DOI: 10.52429/selju.v4i2.670
|View full text |Cite
|
Sign up to set email alerts
|

The Use Of Ice Breakers In Online English Grammar Classes

Abstract: In the English language teaching process, every teaching phase is paramount for the achievement of its goals. At the beginning of the classes, the teachers might bring an ice breaker. Based on the previous studies, ice breaker is considered a crucial component in EFL classes. Considering the prominence of ice breakers, the researcher regards the importance of a literature study about ice breakers, especially in grammar class. English grammar is frequently considered a complicated element. Besides, nowadays, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Distance learning facilitators have employed icebreakers in the past. However, it is worth mentioning that icebreakers should be items that can capture the learners' attention and arouse their interest in the subject (Aniuranti 2021;Wooten, Geerling, and Thomas 200). The main aim of integrating icebreakers into the course is to promote the fun element in class.…”
Section: Constant Weekly Reminders To Learnersmentioning
confidence: 99%
“…Distance learning facilitators have employed icebreakers in the past. However, it is worth mentioning that icebreakers should be items that can capture the learners' attention and arouse their interest in the subject (Aniuranti 2021;Wooten, Geerling, and Thomas 200). The main aim of integrating icebreakers into the course is to promote the fun element in class.…”
Section: Constant Weekly Reminders To Learnersmentioning
confidence: 99%
“…This ice-breaking is always working great. Additionally, Aniuranti (2021) indicated that icebreakers are applied to prepare the student to join the class and introduce the material that is going to be taught. So that students can back focus on their material and teachers back focus on teaching.…”
Section: Messy Classroom Conditionsmentioning
confidence: 99%
“…Ice-breaking activities are considered essential in every teaching and learning process. Implementing ice-breakers at the beginning of the class is assumed as an essential learning stage (Aniuranti, 2021;Aniuranti et al, 2021;Marneni et al, 2017;Yeganehpour & Takkaç, 2016). Before moving into the primary teaching phase, ice breaking is an activity that can be used to reduce students' anxiety and boredom in the classroom, making the teaching and learning process more enjoyable and conducive (Astuti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%